PENINGKATAN KEPEDULIAN KEBERSIHAN PANTAI GORONTALO DI LABUAN BAJO DALAM MEMPERINGATI WORLD OCEAN DAY - Roseven Rudiyanto; Elisabeth Klara Sekar Cahyani; Irna Karina Josephine Kaban; Kusnanto Kusnanto; Joana Viviani (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity was carried out to commemorate World Ocean Day 2022 in Labuan Bajo in the form of a clean Gorontalo Beach on Saturday, June 11, 2022. The activity was attended by 268 participants who were representatives of the Provincial Government of NTT, West Manggarai. The district government, industry, academics, students and teachers from elementary schools around Gorontalo Beach and Labuan Bajo, Bank Indonesia NTT, and the surrounding community. Gorontalo Beach is a destination for local tourists, but the condition is a lot of garbage. The focus of the implementation of activities in the Gorontalo Beach area is 1.1 km long and is divided into ten regions for ten teams. This beach cleaning activity also teaches participants that the collected waste can be divided into three types, namely residual waste, economic value plastic waste, and plastic bottle caps. The amount of waste collected from this activity was 34 kg of plastic waste, 4.8 kg of plastic bottle caps, and 242 kg of residual waste. The collected waste is then transported to be transferred to the next process. In addition, there was an educational session for elementary school students by holding a quiz with prizes on waste management. Based on the evaluation of activities, organic waste in the form of wood and trunks of large trees was also found on Gorontalo Beach. Suggestions that can be made based on these conditions are the use of heavy equipment for cleaning tree trunks to be effective and efficient. In addition, organic waste can be used as raw material for wood crafts and fuel for production houses, such as tofu and brick production.